Assessment of Learning Outcomes in the (Java) Object-Oriented Programming Courses - Biskupic, Ivana Ogrizek; Radovan, Aleksander; Lopatic, Josip (2023 11th International Conference on Information and Education Technology (ICIET), 2023)
The aim of this paper is to obtain students' review on the possible difficulties and workload when mastering the prescribed learning outcomes in object-oriented programming courses based on the JAVA™ programming language. The results of this measurement provide a basis for a possible revision of scheduled hourly rate and consequently ECTS points required for students to achieve the prescribed learning outcomes regarding ESG 2015 guidelines for QA. Perennial experience in teaching indicate that object-oriented programming courses are one of the most demanding in mastering the subject material at the undergraduate level (6 EQF), which is why authors have conducted a survey as part of the JAVA™ course before the final exam at 4 different higher education institutions in the Republic of Croatia. On a scale from 1 to 5 (5 being the highest), students have assessed the difficulty in achieving each learning outcome and also the subjects/topics taught in the course. The results of the survey were compared with the passing results in the summer exams period (academic year 2021/2022 as an additional variable test of the obtained answers). The authors present the summary of their results and provide the conclusion in the context of the subject and course revision regarding curriculum and subject oriented student workload.